Peri-Coronary Sinus Flutter: A Unique Form of an Atypical Atrial Flutter. A Case Report - Ziakos, Athanasios; Greiss, Harald; Sezenias, Angelis; Sause, Armin (Cardiology and Cardiovascular Medicine, 2023)
The coronary sinus musculature connects to the right and the left atrium, forming electrical interatrial bridges and can be a critical part of various left atrial and biatrial flutter circuits. We herein present a rare case of a macroreentrant tachycardia around only the coronary sinus using interatrial connections at its orifice and the inferolateral left atrium and the adjacent left atrial myocardium. Crucial for the identification of this macroreentrant circuit was the record of low voltage signals of epicardial sleeves through an endocardially placed multipolar HD-mapping catheter with small flat electrodes. The peri-Coronary sinus flutter should always be included in the differential diagnosis of an atypical atrial flutter.